2021
DOI: 10.1097/md.0000000000025122
|View full text |Cite
|
Sign up to set email alerts
|

Two years follow-up of golimumab treatment in refractory enteropathic spondyloarthritis patients with Crohn disease

Abstract: Golimumab is a fully human monoclonal antibody against tumor necrosis factor (TNF) approved for the treatment of ulcerative colitis and not for Crohn disease (CD). Many CD patients experience primary, secondary failure, or intolerance to other TNF inhibitors (TNFi) approved in Italy for CD (adalimumab and infliximab). Spondyloarthritis (SpA) may be associated with CD (enteropathic, ESpA) in up to 50% of patients requiring a multidisciplinary and tailored approach. However, only few data from literature and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This study suggest that golimumab may be an alternative therapeutic option for enteropathic spondyloarthropathy in CD patients who are not responsive to other TNF inhibitors. [ 64 ] Certolizumab is a Fab fragment of a recombinant, humanized anti-TNF monoclonal antibody. Studies have shown effectiveness in the treatment of AS, PsA, and CD.…”
Section: Biologic Disease-modifying Antirheumatic Drugs (Bdmards)mentioning
confidence: 99%
“…This study suggest that golimumab may be an alternative therapeutic option for enteropathic spondyloarthropathy in CD patients who are not responsive to other TNF inhibitors. [ 64 ] Certolizumab is a Fab fragment of a recombinant, humanized anti-TNF monoclonal antibody. Studies have shown effectiveness in the treatment of AS, PsA, and CD.…”
Section: Biologic Disease-modifying Antirheumatic Drugs (Bdmards)mentioning
confidence: 99%
“…In our cohort, we did not observe gender differences in the efficacy of GLM, since gender was not a relevant factor in patient outcomes. The high prevalence of IBD in our cohort is due to the early referral in the combined gastro-rheuma outpatient clinic by gastroenterologists from the involved hospitals [ 33 , 34 ]. Thyroid dysfunction may be associated with the worst clinical outcome in several inflammatory conditions and in PsA [ 26 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Male and female patients enrolled in the study had a diagnosis established by a combination of clinical symptoms, endoscopic examination, pathologic examination, and the absence of alternative diagnoses ( Lichtenstein et al, 2018 ). CD activity was classified based on the Crohn’s disease activity index ( Conigliaro et al, 2021 ). The studies involving human participants were reviewed and approved by the China Ethics Committee of Registering Clinical Trials.…”
Section: Methodsmentioning
confidence: 99%